Unveiling the role of SYNGR4 in breast cancer development: a novel target for immunotherapy - Ma, Jie; Wang, Hongtao; Gui, Zhengwei; Yang, Yuanrong (Frontiers in Oncology, 2025)
IntroductionSYNGR4 is considered to be one of the causative genes for amyotrophic lateral sclerosis, but its role in breast cancer development has not been revealed.MethodsThe expression of SYNGR4 in a variety of malignancies including breast cancer was analyzed using Genotype Tissue Expression (GTEx) and the Cancer Genome Atlas (TCGA) databases and verified by specimens collected from our center. The effect of SYNGR4 on breast cancer prognosis was analyzed using bioinformatics and possible pathways by which this molecule affects breast cancer prognosis were explored. The effect of SYNGR4 on immune infiltration of breast cancer was analyzed using GSVA, and the effects of SYNGR4 on breast cancer proliferation, migration, and tumor-associated macrophage polarization in cancer foci were verified by cellular and animal experiments, respectively.ResultsSYNGR4 is highly expressed in a variety of malignant tumors, including breast cancer, and affects the prognosis of breast cancer patients. This may be a volatile effect through Organelle fission, chromosome segregation, nuclear division, etc. SYNGR4 overexpression affects breast cancer proliferation, migration, and tumor immune infiltration, and promotes breast cancer tumor-associated macrophage polarization toward M2.DiscussionSYNGR4 overexpression can affect the prognosis of breast cancer patients by promoting M2 polarization of tumor-associated macrophages in breast cancer, and this molecule may be a novel target for breast cancer immunotherapy.